ASPEK EKONOMI PADA KEHIDUPAN PEREMPUAN LANJUT USIA: Studi Etnografi di Desa Demuk, Kecamatan Pucanglaban, Kabupaten Tulungagung - Richa Meliza; Budiawati Supangkat Iskandar; Rini Susetyawati Soemarwoto (Universitas Andalas, 2019)
Indonesia is predicted to enter the era of bonus demography which is an interesting issue now. This is related to the increasing productive and non-productive population. This phenomenon can benefit the population, both productive and non-productive residents who get less attention, especially economic dependence on nonproductive groups such as the elderly. Elderly are often said to be a burden on society, especially for women who are often associated with domestic work. This study raises the economic independence of elderly women. The method used in this study is a qualitative approach on elderly women in Demuk village, Pucanglaban sub-district, Tulungagung district. Data collection uses participatory observation techniques and in-depth interviews. The results of the study show that elderly women can meet the economic needs of their own family or household. They work in the domestic and public domains such as farmers, laborers, traders, and breeders. Thus elderly women are not burdens, but they become economic support for the family or household.